Variasi Waktu Lama Fermentasi dan Konsentrasi Gula Terhadap Karakteristik Hand sanitizer Kombucha Bunga Telang - Puspitasari, Budiarti; Marlina, Lusi (Universitas Al Azhar Indonesia, 2024)
This study aims to determine the effect of fermentation time and sugar concentration on antibacterial activity in butterfly pea flower Kombucha hand Sanitizer. The experimental design in this study was a Completely Randomized Design (CRD) with variations in fermentation duration of 7 days, 10 days and 14 days and variations in sugar concentration of 20%, 30% and 40%. The testing parameters were the organoleptic test, pH and antibacterial activity. Data analysis used in this research was SPSS (Statistical Package for the Social Sciences) and EXCEL. The procedure of this research is to make kombucha of butterfly pea flower which will then be added during the process of making hand sanitizer. The results of the organoleptic analysis with Kruskal Wallis showed that each treatment did not have a significant difference (Asymp. Sig>0.05). The average value of hand sanitizer pH measurement is 4.47 which indicates that it is by SNI 06-2588: 2017. This antibacterial activity test uses E. coli bacteria with the best results, namely the diameter of the clear zone of 11.4 mm in the A3B3 treatment with a fermentation time of 14 days and a sugar concentration of 40%. This study concludes that the length of fermentation time and sugar concentration affect the antibacterial activity of hand sanitizer.Keywords – Antibacterial, Butterfly Pea, Fermentation, Hand sanitizer, Kombucha